Impact of contracted endodontic cavities on instrumentation efficacy—A systematic review. (27th August 2022) - Shroff, Manan; Kishan, Karkala Venkappa; Shah, Nimisha; Saklecha, Purnima
Abstract: The aim of the present systematic review was to summarise and evaluate the studies comparing the role of contracted endodontic cavities (CECs) and traditional endodontic cavities (TECs) in terms of instrumentation efficacy. The present systematic review comprised of a search of the online databases of Cochrane, PubMed, Google Scholar and grey literature. The articles which were pertaining to instrumentation efficacy in contracted and traditional endodontic cavities were selected based on the PRISMA checklist. Out of the 660 articles which were obtained, irrelevant articles were excluded and a total of 17 articles were selected for this systematic review which assessed the instrumentation efficacy. Eleven studies compared the volume of dentin removed and canal transportation ability. Four studies compared the pulp debridement, and two studies compared the anti‐bacterial efficacy between the two groups. The extrusion of debris between the groups was compared by one study. Out of the 17 studies included, 11 studies proved that contracted endodontic cavities negatively impacted the instrumentation efficacy. Hence, the data suggest that the traditional endodontic access cavities have better results when comparing the instrumentation efficacy.